2023
DOI: 10.1097/tp.0000000000004534
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Transplanting Kidneys From Very Small Pediatric Deceased Donors

Abstract: Background. Kidneys from very small pediatric donors (VSPDs, aged <2 y) are underutilized. Concerns regarding potentially inferior outcomes hinder the use in pediatric recipients. Methods. All pediatric kidney-only transplants from <18-year-old donors between January 2012 and May 2021 in our center were included in this study. Outcomes were compared between VSPD and normal pediatric donor (NPD, aged 2–18 y) groups, and 3-y death-censored graft survival was assessed by the multivariable Cox proportional hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…19,22 Recently, a large single-center study reported on the outcome of mainly single-kidney pediatric KTx from 103 donors <2 y versus 149 donors 2–18 y and found excellent graft survival and similar GFR at 3 y. 16 However, because of the single-center design and donor-recipient size matching protocol, small donor recipients were considerably smaller (15%), potentially leading to overestimation of eGFR in this group. In our study, we found that SDKTx recipients had a superior eGFR at 3 and 5 y than ADKTx recipients, even when performed as single SDKTx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,22 Recently, a large single-center study reported on the outcome of mainly single-kidney pediatric KTx from 103 donors <2 y versus 149 donors 2–18 y and found excellent graft survival and similar GFR at 3 y. 16 However, because of the single-center design and donor-recipient size matching protocol, small donor recipients were considerably smaller (15%), potentially leading to overestimation of eGFR in this group. In our study, we found that SDKTx recipients had a superior eGFR at 3 and 5 y than ADKTx recipients, even when performed as single SDKTx.…”
Section: Discussionmentioning
confidence: 99%
“…10 In contrast to these registry studies, numerous single-center studies have reported excellent outcomes of SDKTx in pediatric recipients, even after a single KTx from very small donors. [11][12][13][14][15][16] Although these studies usually provide more detailed clinical data than registry studies, their generalizability is limited by the lack of a control group and the inherent risk of publication bias.…”
Section: Introductionmentioning
confidence: 99%
“…The process used to recover the pediatric donor kidneys, the back-table preparation method, and the transplant procedures were described in a previous study. [ 4 ] En bloc kidney transplantation was exclusively considered for donors with a body weight less than 5 kg. Graft loss was defined as the irreversible failure of the transplanted kidney, indicated by the need for long-term dialysis, addition to the list for a subsequent kidney transplant, or retransplantation.…”
mentioning
confidence: 99%